Perioperative Management of a Girl with Hemophilia B Undergoing Dorsolumbar Spine Posterior Instrumentation - Martinho, L (2022)
Hemophilia B is a coagulation disorder characterized by a deficiency of clotting factor IX. Women are often heterozygous carriers of the disease, however if their clotting factor levels are less than 60%, they may have an increased bleeding tendency. This is even higher if levels are under 40%. We presente a case of a 14-year-old female, with mild hemofilia B (hemofilia B carrier with factor IX level < 40%) who underwent a major surgery: a posterior spinal instrumentation from D6 to L1. The perioperative management was discussed, including the perioperative administration of blood products and coagulation adjuncts. This was coordinated by a multidisciplinar team (orthopedists, anesthesiologists, hematologists and nurses) to provide the best perioperative care and follow-up. Close collaboration and communication among/with the team members and the patient/family was vital throughout.